(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rise of multiple drug resistant (MDR) bacteria requires a shift from conventional diagnostics to integrated methods that can help explain unpredictable strain-specific antimicrobial responses. This study employed a multi-method characterization strategy of clinical isolates to investigate divergent susceptibility to novel agents. Clinical isolates of Enterococcus faecalis, Bacillus cereus, and two Proteus mirabilis strains were obtained from Sacred Heart Hospital, Abeokuta. Comprehensive profiling included biochemical identification, 16S rRNA gene sequencing, phylogenetic reconstruction, and restriction enzyme analysis. Susceptibility to Nigella sativa seed oil (NSO), biosynthesized silver nanoparticles (AgNPs), and silver nitrate was evaluated using broth micro-dilution and agar well diffusion assays. Phylogenetic analysis confirmed that the two P. mirabilis strains were closely related though restriction enzyme mapping revealed distinct, strain-specific molecular fingerprints. Antimicrobial susceptibility testing showed significant variation. E. faecalis was most susceptible to AgNPs, while P. mirabilis FELIX004 was completely resistant to AgNPs even though susceptible to both NSO and silver nitrate, a paradoxical profile not seen in the closely related susceptible strain FELIX003. Comparative analysis is suggestive of an association between unique restriction patterns in FELIX004 and its AgNP-resistant phenotype. Integrative phenotypic and molecular profiling uncovered substantial intraspecies variation in novel antimicrobial susceptibility testing. The specific paradoxical resistance of P. mirabilis FELIX004 to AgNPs underscores the emergence of agent-specific resistance mechanisms. The study demonstrates that standard phylogenetic relatedness is insufficient to predict strain-specific behavior and highlights the value of multiple approaches for identifying phenotypic outliers that warrant deeper genomic investigation.